2021
DOI: 10.1002/ajpa.24225
|View full text |Cite
|
Sign up to set email alerts
|

Medieval injuries: Skeletal trauma as an indicator of past living conditions and hazard risk in Cambridge, England

Abstract: Objective: To explore how medieval living conditions, occupation, and an individual's role within society impacted their risk of skeletal trauma. Materials: The skeletal remains of 314 individuals from medieval Cambridge that were buried in the parish cemetery of All Saints by the Castle (n = 84), the Augustinian friary (n = 75), and the cemetery of the Hospital of St John the Evangelist (n = 155) were analyzed. Methods: Macroscopic examination and plain radiographs were used to classify fracture type. The cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 64 publications
0
7
0
2
Order By: Relevance
“…Of those, 34 % (n = 55/159) individuals had one or more fractures. Nearly all of the fractures observed in this assemblage occurred antemortem; only one individual (PSN 531) had peri-mortem fractures (see Table 6 ; or Dittmar et al, 2021 for further details ). More males (44 %, n = 38/86) had fractures than did females (32 %, n = 15/47).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Of those, 34 % (n = 55/159) individuals had one or more fractures. Nearly all of the fractures observed in this assemblage occurred antemortem; only one individual (PSN 531) had peri-mortem fractures (see Table 6 ; or Dittmar et al, 2021 for further details ). More males (44 %, n = 38/86) had fractures than did females (32 %, n = 15/47).…”
Section: Resultsmentioning
confidence: 93%
“…However, several individuals within these assemblages had fractures in locations that are commonly associated with interpersonal violence (i.e. cranial vault, mandible, ribs) (see Dittmar et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most clavicle fractures in the RD group were oblique fractures at midshaft (Figure 5), with a visible fracture line extending diagonally across the longitudinal axis (Dittmar et al, 2021;Lovell, 2008;Waldron, 2009), while no clavicle fracture was observed in the LIS group.…”
Section: Discussionmentioning
confidence: 96%
“…This difference was statistically significant only for the clavicle between the Hungarian group with riding deposit (RD) and the comparison group from Lisbon (LIS), in particular (Table 2 and Figure 3). Most clavicle fractures in the RD group were oblique fractures at midshaft (Figure 5), with a visible fracture line extending diagonally across the longitudinal axis (Dittmar et al, 2021; Lovell, 2008; Waldron, 2009), while no clavicle fracture was observed in the LIS group.…”
Section: Discussionmentioning
confidence: 99%